Obstructive Sleep Apnea and Hypertension - Okcay, Aynur (J Clin Hypertens (Greenwich), 2008)
There has long been a recognized link between obstructive sleep apnea (OSA) and the cardiovascular system, no aspect of which has been more studied than blood pressure. Research in OSA has not only demonstrated dysregulation of homeostatic cardiovascular mechanisms but also has furthered our understanding of blood pressure regulatory control. Acute nocturnal blood pressure elevations associated with disordered breathing events have been reproduced from a number of observational studies, the accrual of which has also made an increasing argument for the importance of OSA in the pathogenesis of diurnal hypertension, as suggested by the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC 7), which implicated OSA as a secondary cause of hypertension. Accumulating data from randomized controlled treatment trials in OSA, particularly with continuous positive airway pressure, though sometimes inconsistent, suggest a potential role in blood pressure reduction. Further research is needed to better clarify indications for OSA treatment as well as its role as an adjunct to other antihypertensive treatments.